Effectiveness of the Implementation of the Provincial Liaison Agency Bangka Belitung Islands - Lara Meireini; Baharuddin Thahir; Ela L. Wargadinata (INFOKUM, 2025)
This research is motivated by the importance of the role of the Liaison Agency as an extension of the Bangka Belitung Islands Provincial Government at the central level, especially in establishing coordination between institutions, promoting arts and culture, and implementing protocol functions. Despite its strategic position, these functions have not been running optimally as mandated in Governor Regulation Number 7 of 2021. This study aims to analyze the effectiveness of the implementation of the Liaison Agency function and identify the factors that support and inhibit it. This study uses the theory of organizational effectiveness from Gibson et al. (2000) with five main indicators: satisfaction, productivity, efficiency, adaptability, and development. Organizational theory and decentralization theory are also used as conceptual frameworks. The method used is descriptive qualitative with data collection techniques through interviews, observations, and document studies. The results of the study show that the implementation of the Liaison Agency function of the Bangka Belitung Islands Province is quite effective but still faces a number of structural and operational challenges. On the one hand, there are supporting factors such as a conducive work environment, quite effective coordination between sections, and efforts to utilize technology and continuous training even with a limited budget. However, on the other hand, this success is limited by serious obstacles, including outdated work facilities, the absence of expensive allowances for ASN in Jakarta, an unbalanced workload due to limited human resources, and a promotion and career system that is not yet transparent and performance-based. Budget management is considered quite efficient, but not yet optimal in supporting the achievement of overall activity targets. Thus, although several aspects show positive performance, the overall effectiveness of the organization still requires significant improvements in terms of strengthening human resources, updating facilities, and reforming the career system so that the Liaison Agency function can be carried out optimally and sustainably.